MANAJEMEN HUTAN RAKYAT: PERBANDINGAN HUTAN RAKYAT BERSERTIFIKASI LESTARI DENGAN HUTAN RAKYAT BELUM BERSERTIFIKASI (Studi Kasus Hutan Rakyat di Kabupaten Gunung Kidul dan Kabupaten Cianjur) - , FIRMAN DERMAWAN YUDA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Development of privately owned forest give one hope for the fulfillment of the wood raw material or for the purpose of national exports. Privately owned forest also provides improvements to the environment by growing trees on community land. Privately owned forest certification is one way to gain recognition of sustainable forest management by the community and are expected to be a way for the market incentives and support the Government's policy towards the privately owned forest. This research aims to: 1) looking for data and an explanation of the certified privately owned forest management and non-certified privately owned forest management, 2) looking for data and an explanation of the certified privately owned forest institutional and non-certified privately owned forest institutional. The research was conducted in two locations: Dengok Village Playen District Gunung Kidul Regency represents certified privately owned forest and Mekargalih Village Cikalongkulon District Cianjur Regency represents noncertified privately owned forest. The basic method used in this study is a survey methods. Analysis was used in this study is descriptive analysis. Privately owned forest management on both areas carried out by farmers because the people's forest management are still individual action. Implementation of forest management is done on both privately owned forest apply traditional silviculture and commonly carried out by farmers who are marked by intercropping cultivation system. In these two areas have been formed institutions as a place for forest farmer. In both areas, generally timber marketing directly to traders/collectors in tree stand, where the determinant price is the buyer and farmers do not have any bargaining position just as price takers.. Privately owned forests in both areas are equally contributed income on average 47% to Dengok Village and Mekargalih Village 55,17%. Income from the privately owned forest in Dengok Village is Rp. 24.436.327/ha/year with teak trees, more big than Mekargalih Village Rp. 7.155.121/ha/year with forest sengon. With the certification, farmers in the Dengok Village gives the benefit of adding knowledge. Privately owned forests in both areas are equally provides benefits in the form of the establishment of environment a good micro-climate and hydrological functions.